Analisis faktor kinerja keuangan bank BRI - Siregar , Ayu Wulan Sari (ARKA INSTITUTE, 2022)
The health condition of the Bank can be analyzed through financial statements, which provide valuable information for decision-making. This study aims to analyze the factors affecting the financial performance of BRI Bank using a quantitative approach. The research is quantitative, with secondary data sources, and employs a causal associative method. Sampling criteria include complete and audited reports, encompassing all relevant financial information for analysis. In this causal research, data analysis techniques are utilized to identify the causal relationships between the existing variables. The results show that BOPO has a negative and significant effect on ROA, while CAR has a negative but not significant effect on ROA. Additionally, NPF and FDR have positive but insignificant effects on ROA. It can be concluded that CAR, NPF, BOPO, and FDR influence ROA at Bank BRI, with significant effects.